ANTIMICROBIAL STUDIES OF ALLICIN AND AJOENE - F.REHMAN; SAMYA MAIRAJ (International Journal of Pharma and Bio Sciences, 2013)
Garlic(.allium sativum) has been shown to inhibit the growth of variety of microorganisms.The antimicrobial activity of garlic is believed to be due to the effect of allicin and ajoene.The transformation of allicin to ajoene is summarized. The broad spectrum antimicrobial effects of allicin and ajoene are due to the multiple inhibitory effects on various thiol dependent enzymatic systems.. The antimicrobial activity of different concentration of allicin and ajoene were measured by determining the growth of test fungus and bacteria by dry weight increased method and by agar diffusion method against Aspergillus flavus, Aspergillus niger,Cryptococcus neoformons and Alternaria alternate fungi.Streproproteus, Staphylococcus & E.Coli bacteria. The results indicate that ajoene has more antimicrobial as compare to allicin. The activity index for different microbes have also been calculated.